Immortality on ice - Engle, Larry; Hayes, Bill; Wilcher, Deanie; Caliandro, Tom (Discovery Channel, 1996)
"Offers an intriguing perspective on the strange frozen world of cryonics -- human preservation through freezing in the hope that tomorrow's advanced technology can transcend death, disease and aging -- its supporters and its critics, and its incredible promise of life after death.